Estimation of Mean Variation in Prediction Probability for Prevalence of Hypertension in Middle-Aged and Older Chinese Using Probit Model. (May 2020) - Yin, Minghui; Liu, Caiping
The aims of this study are to estimate the mean change in the predicted probability and identify the most important predictors of diagnosed, measured, total, and undiagnosed hypertension among aged 45+ adults in China. We used data collected from the fourth wave (2015) of the China Health and Retirement Longitudinal Study (n = 12 236). First, we estimated the prevalence of diagnosed, measured, total, and undiagnosed hypertension. Second, we used probit models to identify the factors that were associated with hypertension, and we estimated average marginal effects of variables in probit models. Among Chinese people aged 45+, the prevalence of diagnosed, measured, total, and undiagnosed hypertension were 23.1%, 32.7%, 42.6%, and 19.5%, respectively. The probability of total hypertension is higher for overweight and obesity than normal body mass index (10.4% and 19.3%, respectively), higher for past smokers and current smokers than nonsmokers (5.9% and 3.8%, respectively), higher for urban population than rural population (4.0%), and lower for married individuals than unmarried/single (−7.1%). Our results suggest that continued strengthening for smoking prevention is needed to reduce smoking-related hypertension and greater focus on prevention of hypertension are necessary for overweight or obesity and in urban areas among middle-aged and older adults in China.